Nutritional care for the enhancement of body beauty (Research, Society and Development, 2022)
People from all walks of life have been looking for professionals from different areas to meet their health, rejuvenation and beauty needs. This search made several professionals, including nutritionists, improve themselves more. Nutrition in aesthetics goes beyond diet therapy: it implements nutritional care taking into account the aesthetic needs of your patient. This study aims to review nutritional care to enhance body beauty. This is an integrative review study, where a search was carried out in the following databases: Scientific Electronic Library Online (SciELO), Latin American and Caribbean Literature in Health Sciences (LILACS) and Spanish Bibliographic Index in Sciences of Health (IBECS). The following descriptors were used to search for articles: “Food, Diet and Nutrition”, “Beauty Industry” and “Physical Appearance”. The inclusion criteria defined for the selection of articles were: articles available online, in full, in Portuguese, English and Spanish, and indexed in the aforementioned databases in the years 2017 to 2022. As exclusion criteria: articles that did not include the theme and repeated studies in the databases. People notice that beauty care is everyone's goal, and dedication to aesthetics is expanding every day. This method has a detrimental impact on self-image, particularly for women who feel an urge to lose weight. Cultural pressure to lose weight is a simple means of etiology of eating disorders and interacts with biological, psychological and family factors.